Fostering Sustainable Tourism Development in Merauke through Community-Based Tourism - Machya Astuti Dewi; Iva Rachmawati; sri Issundari; Meilan Sugiarto (Yogyakarta State University, 2019)
Merauke is located in the eastern part of Indonesia that is rich of natural and cultural resources potential for tourism. Tourism could be a solution to reduce poverty, especially through community-based tourism. Communities reap economic benefits from tourism industry by the increase of local income, hence the social welfare. On the contrary, poor management may lead the emerging Merauke tourism into environmental ecosystem damage. Such a threat to environmental sustainability outweighs any economic benefits because future generation will suffer from the inherited damaged environment. This article will discuss Merauke community participation in fostering the development of sustainable tourism through community-based tourism, that is maintaining sustainability of the environment and ecosystem while considering local communities sociocultural conditions. In doing so, this study uses a descriptive-qualitative approach. Data was collected from document tracking and interviews with Merauke Regional Government, WWF activists, and community leaders. The findings indicated that local communities supported Merauke tourism by developing entrepreneurship in tourism industry, increasing community social control in protecting the environment and enhancing the role of local customary leaders in supporting the tourism development.